2020
DOI: 10.1186/s13104-020-05318-5
|View full text |Cite
|
Sign up to set email alerts
|

Unidentified dengue serotypes in DENV positive samples and detection of other pathogens responsible for an acute febrile illness outbreak 2016 in Cajamarca, Peru

Abstract: Objective To describe the prevalence of dengue virus serotypes, as well as other viral and bacterial pathogens that cause acute febrile illness during an outbreak in Cajamarca in 2016. Results Dengue virus (DENV) was the most frequent etiologic agent detected in 25.8% of samples (32/124), followed by Rickettsia spp. in 8.1% (10/124), Zika virus in 4.8% (6/124), Chikungunya virus 2.4% (3/124) and Bartonella bacilliformis 1.6% (2/124) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
(47 reference statements)
0
7
0
Order By: Relevance
“…This is because the symptoms of the patient with Oropouche fever were very similar to those of other arboviral diseases and not specific to Oropouche infection [ 5 ]. This does not help with the prediction or diagnosis of OROV disease [ 3 ], especially in endemic areas of coinfection of these diseases [ 5 , 27 ]. The findings of this study are similar to other studies that described the typical clinical manifestations such as fever, headache, myalgia, arthralgia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is because the symptoms of the patient with Oropouche fever were very similar to those of other arboviral diseases and not specific to Oropouche infection [ 5 ]. This does not help with the prediction or diagnosis of OROV disease [ 3 ], especially in endemic areas of coinfection of these diseases [ 5 , 27 ]. The findings of this study are similar to other studies that described the typical clinical manifestations such as fever, headache, myalgia, arthralgia.…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, the variable odynophagia was the only one that was positively associated with the clinical diagnosis of OROV using the CPR. Therefore, symptomatology is probably not useful to build a clinical prediction model, especially in a country like Peru, in which there is a high prevalence of arboviral diseases that end up overlapping because they are differential diagnoses [ 27 , 28 ]. These findings are consistent with other studies where it was found that the etiological clinical diagnosis of OROV infection was not possible due to the low specificity of the symptoms, which is why molecular diagnosis is recommended [ 15 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This province is located at a mean altitude of 729 masl and has warm tropical weather with an annual mean temperature of 24.2°C. Several pathogens responsible for AFI have been reported in this region, which include DENV, Oropouche virus (OROV), ZIKV, leptospirosis, bartonelosis, rickettsia, and malaria, among others [ 8 , 9 , 14 ].…”
Section: Methodsmentioning
confidence: 99%